2020
DOI: 10.1016/j.jalz.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic, axonal damage and inflammatory cerebrospinal fluid biomarkers in neurodegenerative dementias

Abstract: Introduction: Synaptic damage, axonal neurodegeneration, and neuroinflammation are common features in Alzheimer's disease (AD), frontotemporal dementia (FTD), and Creutzfeldt-Jakob disease (CJD). Methods: Unicentric cohort of 353 participants included healthy control (HC) subjects, AD continuum stages, genetic AD and FTD, and FTD and CJD. We measured cerebrospinal fluid neurofilament light (NF-L), neurogranin (Ng), 14-3-3, and YKL-40 proteins.Results: Biomarkers showed differences in HC subjects versus AD, FTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 45 publications
5
51
0
2
Order By: Relevance
“…They have also been genetically linked to both neurodegenerative diseases (PD, AD, and CJD) and neuropsychiatric disorders (schizophrenia and bipolar disorder). 268,269 A recent study by Antonell et al 270 found significantly increased gamma 14-3-3 concentrations in both FTD and AD compared with controls. For AD, increased concentrations were found already in a prodromal stage and the protein level was also significantly higher at later stages compared with FTD.…”
Section: Miscellaneous: Other Emerging Synaptic Biomarkersmentioning
confidence: 96%
“…They have also been genetically linked to both neurodegenerative diseases (PD, AD, and CJD) and neuropsychiatric disorders (schizophrenia and bipolar disorder). 268,269 A recent study by Antonell et al 270 found significantly increased gamma 14-3-3 concentrations in both FTD and AD compared with controls. For AD, increased concentrations were found already in a prodromal stage and the protein level was also significantly higher at later stages compared with FTD.…”
Section: Miscellaneous: Other Emerging Synaptic Biomarkersmentioning
confidence: 96%
“…However, the authors did not consider CSF Ng as a specific marker of synaptic degeneration but rather a marker of neuronal damage ( Blennow et al, 2019 ). A recent study had a unicentric cohort of 353 participants, including HC subjects, AD, frontotemporal dementia (FTD), and CJD ( Antonell et al, 2020 ). They analyzed and compared the diagnostic accuracy and differentiating capacity of four noncore biomarkers, which stand for the distinct aspects of the neurodegeneration process ( Antonell et al, 2020 ).…”
Section: Associations Between Neurogranin and Neurological And Mentalmentioning
confidence: 99%
“…A recent study had a unicentric cohort of 353 participants, including HC subjects, AD, frontotemporal dementia (FTD), and CJD ( Antonell et al, 2020 ). They analyzed and compared the diagnostic accuracy and differentiating capacity of four noncore biomarkers, which stand for the distinct aspects of the neurodegeneration process ( Antonell et al, 2020 ). The rank of CSF Ng concentrations from lower to higher is FTD < HC < AD < CJD, which is in concordance with previously published data.…”
Section: Associations Between Neurogranin and Neurological And Mentalmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no cure for AD, only ve prescription drugs were approved to intend for symptom management, with varying degrees of e cacy [2]. With the deepening of studies, some theories, such as amyloid β (Aβ) deposition, tau protein abnormality, axonal transport defect, in ammatory response, and cholinergic damage, etc, have been gradually recognized [3][4][5]. The clinical and genetic trials of more-effective Alzheimer's drugs targeting anti-amyloid, anti-neuroin ammation, anti-tau, or neuroprotection are ongoing.…”
Section: Introductionmentioning
confidence: 99%